Dietary glycemic index, glycemic load, and risk of COVID-19: a prospective cohort study - Elahe Shamshirgardi; Seyed Jalil Masoumi; Asma Kazemi; Mehran Nouri; Zeynab Shahsavani; Cain C. T. Clark; Mehrdad Behzadi; Marzieh Akbarzadeh (Journal of Health, Population and Nutrition)
Abstract Background Considering the associations of insulin resistance and glycemic control with immunity, the present study sought to evaluate the association between dietary glycemic index (GI) and glycemic load (GL), as the main dietary determinants of these conditions, with the risk of COVID-19 infection in the participants of Shiraz University of Medical Sciences employees’ health cohort. Methods In this prospective study, data from 3319 cohort study participants were analyzed. Demographic, anthropometric and dietary intake data were collected at the time of recruitment. Dietary GI and GL were calculated based on the data from the food frequency questionnaire. In the follow-ups, data on COVID-19 infection were recorded. To investigate the associations between dietary GI and GL with COVID-19, Cox regression statistics were used. Analysis of variance was used to compare the rate of COVID-19 infection in the tertiles of GI and GL. Results The mean age of the participants was 40.92 ± 6.99 years. Of these, 210 cases with COVID-19 were recorded. The hazard ratios of COVID-19 infection in the second and third tertile of the GI were 3.44 (95% CI = 2.13–5.55) and 6.45 (95% CI = 4.11–10.12) times greater than in the first tertile, respectively. Also, this risk ratio in the second and third tertile of the GL was 8.78 (95% CI = 4.62–16.69) and 54.04 (95% CI = 27.18–107.46) times more than in the first tertile. Conclusions The present study showed a higher risk of COVID-19 infection in higher tertiles of dietary GI and GL.